A LITERATURE REVIEW: CHOOSING THE RIGHT LEARNING MODEL FOR MATHEMATICS LEARNING - Dave Marcellino Sancia (Afore : Jurnal Pendidikan Matematika, 2025)
This research is motivated by the need to find the most appropriate mathematics learning model to improve the effectiveness and quality of the learning process. The purpose of this study is to identify and analyze the advantages and limitations of various mathematics learning models through literature studies. The type of research used is a literature review with data sources in the form of 17 journal articles. Data were collected through documentation techniques and analyzed descriptively-comparatively by reviewing the similarities and differences in the findings of each article. The results show that each learning model has different effectiveness according to the purpose and context of its application. PBL and PjBL models are effective for developing higher-order thinking skills, while Discovery Learning and RME excel in building conceptual understanding, and Cooperative Learning improves student collaboration. This study suggests the application of models in a combinative and adaptive manner.